A geographical analysis of farming in East Griqualand - Leslie, Kathryn Ann (Rhodes University, Faculty of Science, Department of Geography, 1985)
From Preface: The study focusses on spatial aspects of farming and particularly how di stance from marketing centres influences farming activity. However, not all aspects of farming activity could be given close attention due to the limited time and funds available and it was decided to isolate two aspects of farming activity for detailed study, namely, farm size and intensity. Other variables, such as land-use, are looked at in relation to the two main variables. Although East Griqualand is the general area selected for study, for practical purposes it was decided to select areas within East Griqualand for an in-depth study. As the study focusses on the influence of distance from marketing centres on farming activity, it was decided to select marketing centres in East Griqualand around which farming takes place. There are six of these centres in East Griqualand, that is, Kokstad, Matatiele, Cedarville, Franklin, Swartberg and New Amalfi. Two marketing centres, Cedarville and Swartberg, were selected and the farms served by these centres became the two sub-areas in which the research was conducted. The selection of the marketing centres and the justification for this selection is discussed in Chapter Four. A problem arose when calculating the distance from the farming unit to the marketing centre where a single set of books is kept even though the farming unit does not consist of one contiguous area. It was, however, found that all farmers conduct farming operations from a central farm, usually that on which they reside and on which farming implements and other farming requirements are stored. The distance was therefore calculated from the farm gate of the farm from which farming operations are controlled. The general study area is show in Figure 6. However, it was difficult to delimit the exact study area on the map as many of the farm boundaries were imperfectly known by farmers and were considered confidential information by local agricultural officials. The two sub-areas consist of the areas surrounding the marketing centres of Cedarville and Swartberg respectively. As a study of this nature has not previously been conducted in East Griqualand, it was decided that the study should constitute a pilot survey. As such, the study is a preliminary survey aimed at identifying general trends of the relationship between distance to marketing centres, farm size and intensity of fanning in the selected areas. The study could therefore be used to provide pointers for further research and act as a basis for a more comprehensive study of the same nature in East Griqualand.
Keywords: Agriculture -- Griqualand East (South Africa); Rural development -- Griqualand East (South Africa); Agricultural deography -- Griqualand East (South Africa); Geography -- Methodology; Infrastructure (Economics) -- Griqualand East (South Africa)